Regulated delayed attenuation enhances the immunogenicity and protection provided by recombinant Salmonella enterica serovar Typhimurium vaccines expressing serovar Choleraesuis O-polysaccharides. Issue 33 (9th August 2018) - Zhao, Xinxin; Liang, Sheng; Dai, Qinlong; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Wang, Mingshu; Chen, Shun; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Zhang, Ling; et al.
Abstract: Regulated delayed attenuation is a well-studied strategy for retaining the immunogenicity of Salmonella -vectored vaccines. In this study, this strategy was used to optimize two previously constructed recombinant Salmonella enterica serovar Typhimurium vaccines expressing S. Choleraesuis O-polysaccharides (OPS). The novel vaccine strains SLT31 (Δ asd Δ rmlB-rfbP ΔPcrp ::T araC PBAD ) and SLT33 (Δ asd Δ rfbP Δ pagL ::T araC PBAD rfbP ΔP crp ::T araC PBAD ) were constructed by replacement of the native crp promoter with the arabinose-dependent araC PBAD promoter. As controls, two vaccine strains with direct crp mutations were also constructed, namely, SLT30 (Δ asd Δ rmlB - rfbP Δ crp ) and SLT32 (Δ asd Δ rfbP Δ pagL ::T araC PBAD rfbP Δ crp ). Then, the ability to deliver the heterologous S. Choleraesuis OPS on the Asd + plasmid pCZ1 to the mouse immune system was evaluated in the strains with or without regulated delayed attenuation. The SLT30 (pCZ1) and SLT31 (pCZ1) strains expressed only the heterologous OPS, while the SLT32 (pCZ1) and SLT33 (pCZ1) strains co-expressed the homologous and heterologous OPS. The strain SLT31 (pCZ1) or SLT33 (pCZ1), which exhibited regulated delayed attenuation, colonized mouse tissues significantly better and stimulated stronger antibody responses against S. Choleraesuis LPS post immunization than the SLT30 (pCZ1) or SLT32 (pCZ1) strain. Immunization with SLT31 (pCZ1) or SLT33 (pCZ1) resulted in a significant reduction in bacterial loads in mouse tissues and a greater degree of protection against a lethal S. Choleraesuis dose compared with the effects observed after SLT30 (pCZ1) or SLT32 (pCZ1) immunization (100% vs. 80% or 70% vs. 50%, respectively). In addition, all four vaccines conferred complete protection against S. Typhimurium challenge. Overall, our study demonstrates that regulated delayed attenuation via an araC PBAD -regulated crp gene can enhance the cross-protection by Salmonella -vectored vaccines expressing heterologous OPS, and strain SLT31 (pCZ1) is a good candidate vaccine for preventing both S. Typhimurium and S. Choleraesuis infections.